Analysis of the Effect of Social Media Usage, Search Engine Optimization, and Content Strategy on Business Growth in the E-Commerce Industry in Indonesia - Sinaga, Hommy Dorthy Ellyany; Syamsulbahri, Syamsulbahri; Muhajir, Ali; Darmayanti, Novi (West Science Journal Economic and Entrepreneurship, 2024)
This research investigates the influence of digital marketing practices on business growth in the e-commerce industry in Indonesia, focusing on Social Media Usage, Search Engine Optimization (SEO), and Content Strategy. A sample of 150 e-commerce businesses was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results reveal significant positive relationships between Social Media Usage, SEO, and Content Strategy with Business Growth. Additionally, mediation and moderation effects are explored, suggesting a significant mediating role of customer engagement in the relationship between social media usage and business growth. The findings provide practical implications for businesses and policymakers in enhancing digital marketing strategies for sustainable growth in the dynamic Indonesian e-commerce landscape.